Can electronic screens influence head and neck posture in adolescents? A systematic review - Aline Mendonça Turci; Camila Gorla Nogueira; Michelli Belotti Bersanetti (Fisioterapia e Pesquisa)
ABSTRACT This systematic review aims to identify whether electronic screens can influence head and neck posture in adolescents. This study was registered in PROSPERO and the databases used were EMBASE, LILACS, SciELO, PEDro, PubMed, and Scopus, with no language or publication date limitations. The keywords used were posture, neck, and adolescents. A total of 1,997 articles with duplicates were found, 1,858 articles were excluded after title reading and 65 after abstract reading. During the analysis of the full texts, 22 were excluded because they addressed individuals with an average age of less than 15 or more than 19 years, 10 did not refer to technology use, and three only evaluated symptomatic individuals, therefore, only four articles were reviewed. The methodological quality of the studies was defined according to the Newcastle Ottawa Quality Assessment Scale, with three being classified as good methodological quality and analyzing posture when using a computer, and one with poor quality that analyzed posture when using a smartphone. Therefore, regarding smartphone use, considerations are limited. Overall, computer use is not responsible for postural changes in the head and neck of adolescents; however, more studies are needed to confirm this conclusion.